Imatinib-resistance without BCR/ABL Point Mutation in Chronic Myeloid Leukemia - Aytan Shirinova (Caucasian Medical Journal)
Chronic myeloid leukemia (CML) is a myeloproliferative bone marrow neoplasm that occurs because of a fusion gene called BCR-ABL1. Imatinib -the inhibitor of this fusion geneis the target therapy in CML. But unfortunately, resistance against imatinib occurs in some patients. In September 2019 47-year-old male was diagnosed with CML-chronic phase and intermediate risk group. Imatinib has been prescribed as a first-line treatment. The patient did not achieve a major molecular response (MMR). Next-generation sequencing using a 54 myeloid-targeted gene panel was negative for ABL1 L248V, G250E, Y253H, E255K, F311L, T315I, F317L, F311I, M351T, and other point mutations. After Nilotinib patient achieved MMR within two years. Imatinib resistance is impediment during treating CML. In the future, new molecules for BCR-ABL inhibitors, combination therapy, and molecules entering the blood-brain barrier may improve the outcomes of therapy and prevent imatinib resistance in CML.